#TITLE_ALTERNATIVE# - YUNIASTRIA (NIM 13704023); Pembimbing: Dr. Ir. Husaini Ardy, FITRI
High temperature corrosion is a serious problem on the reformer tubes because they encounter severe corrosive environments. These tubes are found to be corroded via oxidation, sulfidation, and molten salt corrosion. Molten salt corrosion occurs by the formation of alkali-iron sulfate as reaction products of alkali sulfate deposite from the coal combustion with base metal. The corrosion process will be more severe when the deposite contain sodium chloride from seawater. Through several experiments and characterizations, the behaviors of high temperature corrosion on reformer tube were studied. The molten salt corrosion attack were simulated by applying synthetic salts deposite of Na2SO4, K2SO4, and NaCl onto the reformer tubes specimens. The specimens were heated to 950 0C and the exposure time was varied from 12, 24, to 36 hours. The corrosion behaviors were investigated by weight change, metallography, depth of attacks, and chemical composition of corrosion products. The results of this research are with variation of salts deposite composition and exposure time, there is a difference corrosion rate on specimens. The most severe corrosion was found on specimens which coated with 80% Na2SO4/ 10% K2SO4/ 10 % NaCl after 36 hours exposure time. The weight gain for this specimen is 0,813 gr/cm 2 and the depth of corrosion attack is 1,44 mm. The corrosion attack that caused by molten salt of sulfate and sodium chloride revealed as intergranular form. This intergranular attack formed as the result of sulfur and chlorine attack to primary carbides at grain boundaries.